Internalisasi Pendidikan Karakter Islami Anak Ditengah Pandemi Covid-19 - Hilda Afrilia; Indriya Indriya (Al-Fikr: Jurnal Pendidikan Islam, 2020)
This research aims to find out how families play in the planting of Islamic character education in children during the COVID-19 outbreak. The research method uses descriptive qualitative methods. While the data purposive sampling techniques with questionnaire-assisted instruments from Google. The analysis of the data used is qualitatively descriptive. The results show that with the government's policy of closing schools and doing distance learning due to the COVID-19 pandemic, Islamic character education planting in children during the COVID-19 pandemic is in desperate need of family roles. The role of the family is very important because the family is the nearest neighborhood of the child and also the informal educational institution of the child early on, especially the parent who is the first madrassa for the child. to apply Islamic character education is also needed efforts are made so that the character of Islami is attached to the child until adulthood later that will be discussed in this research.